Identification and Characterization of Neuropeptides and Their G Protein-Coupled Receptors (GPCRs) in the Cowpea Aphid Aphis craccivora - Li, Xiao; Du, Long; Jiang, Xiao-Jing; Ju, Qian; Qu, Chun-Juan; Qu, Ming-Jing; Liu, Tong-Xian (Frontiers in Endocrinology, 2020)
Neuropeptides are the most abundant and diverse signal molecules in insects. They act as neurohormones and neuromodulators to regulate the physiology and behaviour of insects. The majority of neuropeptides initiate downstream signalling pathways through binding to G protein-coupled receptors (GPCRs) on the cell surface. In this study, RNA-seq technology and bioinformatics were used to search for genes encoding neuropeptides and their GPCRs in the cowpea aphid Aphis craccivora. And the expression of these genes at different developmental stages of A. craccivora was analysed by quantitative real-time PCR (qRT-PCR). A total of 40 candidate genes encoding neuropeptide precursors were identified from the transcriptome data, which is roughly equivalent to the number of neuropeptide genes that have been reported in other insects. On this basis, software analysis combined with homologous prediction estimated that there could be more than 60 mature neuropeptides with biological activity. In addition, 46 neuropeptide GPCRs were obtained, of which 40 belong to rhodopsin-like receptors (A-family GPCRs), including 21 families of neuropeptide receptors and 7 orphan receptors, and 6 belong to secretin-like receptors (B-family GPCRs), including diuretic hormone 31 (DH31), DH44 and pigment-dispersing factor (PDF) receptors. Compared with holometabolous insects such as Drosophila melanogaster, the coding genes for sulfakinin, corazonin, arginine vasopressin-like peptide (AVLP) and trissin and the corresponding receptors were not found in A. craccivora. It is speculated that A. craccivora likely lacks the above neuropeptide signalling pathways, which is consistent with Acyrthosiphon pisum and that the loss of these pathways may be a common feature of aphids. In addition, expression profiling revealed neuropeptide genes and their GPCR genes that are differentially expressed at different developmental stages and in different wing morphs. This study will help to deepen our understanding of the neuropeptide signalling systems in aphids, thus laying the foundation for the development of new methods for aphid control targeting these signalling systems.